The impact of elementary school children’s favorite cartoon shows on children’s imitation behavior - Atiqa Sabardila; Markhamah Markhamah; Agus Budi Wahyudi; Hari Kusmanto; Lathifah Nurul Hidayah; Duwi Saputo (ProTVF, 2023)
Background: Popular children’s television shows are thought to imitate elementary school children’s language behavior. If children do not get parental assistance, television viewing can have an adverse effect on children’s behavior. Purpose: Therefore, this study aims to examine the influence of children’s television shows on the imitation behavior of elementary-age children. Methods: This study took a descriptive-qualitative approach. In-depth interviews with parents of elementary-age children who watch television were used to collect data for this study. The data analysis employed the interactive model. Results: This study found various imitations such as (1) linguistic imitation, children mimic the language used in television shows and add new vocabulary; (2) behavioral imitation, including both positive and negative behaviors. Positive habits include: Dancing, helping to cook like Bald, imitating the call to prayer, and reciting the Koran. Negative habits include language training, listening to adhan, singing, eating independently, understanding the show, reading, sharing food, practicing prayers, and mimicking adhan. Based on the impact of the shows, it is evident that not all children’s television shows positively impact their language and behavior. Implications: Theoretically, this research implies that elementary school children’s imitation behavior can be formed through television shows that children watch. The practical implications of this research are as input for parents and teachers to have television shows that children watch as a medium for elementary school children’s education.